The Evolution of Fairy Tale Motifs in A Little Princess and Matilda - Ayyıldız, Nilay Erdem (My University, 2025)
Traditional western fairy tales have a significant impact on the perpetuation of patriarchal ideology throughout the ages. This study argues that two selected children's novels revolving around female protagonists, Frances Hodgson Burnett’s The Little Princess (1905) and Roald Dahl’s Matilda (1988), draw on the fairy tale framework. However, it also asserts that they use fairy tale elements in different ways, depending on the socio-cultural changes that have developed over the years. Therefore, the study discusses to what extent these novels continue or subvert the classical fairy tale tradition through the identification of character traits, motifs and plot. For this purpose, a feminist approach, particularly intersectional feminism, is employed to study the novels. The term “intersectionality,” coined by Kimberlé Crenshaw (1989) proposes the notion that gender roles, accompanied by many other factors such as race, sexuality and socio-economic status result in the subordination of women. The intersectional feminist approach to the selected novels reveals that character formation, motifs and the use of plot differ in children's novels, breaking the classical western fairy tale tradition because of the alteration in power dynamics in the British society in time, influencing the female protagonists’ social identities within an integrative perspective. In this context, this study intends to contribute to the literature by revealing the changes in approaches to gender issues and the evolution of fairy tale motifs over time through a comparative intersectional feminist reading of Burnett’s The Little Princess and Dahl’s Matilda.
Keywords: Patriarchal Ideology; Fairy Tales; Matilda; Children’s Novels; A Little Princess